Maternal Socio-Economic Status and the Well-Being of the Next Generation(s) - Kasey Buckles (Institute of Labor Economics (IZA), 2017)
A rich literature in economics and the social sciences has shown that improvements in women's socio-economic status (SES) can also improve the well-being of their children. This chapter identifies several channels for this effect, drawing on both theoretical and empirical work in economics. Empirical evidence on the effects of maternal SES on child outcomes like health, education, and labor market success is presented, with a focus on recent work using new data sets and methodological innovations that allow for credible identification. The chapter also discusses emerging evidence that shocks to maternal well-being can affect not only a woman's own children, but future generations as well. Finally, the chapter highlights several fertile areas for future work.
Keywords: I14; I24; I3; J1; 330; maternal socio-economic status; intergenerational transmission of education; intergenerational transmission of income; child well-being; infant health; child health; child quality production function